2022
DOI: 10.1210/clinem/dgac218
|View full text |Cite
|
Sign up to set email alerts
|

Defining Reference Ranges for Serum Anti-Müllerian Hormone on a Large Cohort of Normozoospermic Adult Men Highlights New Potential Physiological Functions of AMH on FSH Secretion and Sperm Motility

Abstract: Background Few studies to date have attempted to measure serum anti-Müllerian hormone (AMH) levels in adult men, and solid references ranges have not yet been defined on a large cohort. Objective In this study, we aimed to first establish the reference ranges for serum AMH and AMH-to-total testosterone ratio (AMH/tT) in adult males. Secondly, we investigated the relationship between serum AMH and both reproductive hormones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
2
10
0
2
Order By: Relevance
“…Ideally, the observed differences in reproductive hormones between AMH groups could be supported by evaluation of testis histology, but despite this limitation, it is unlikely that men with low serum AMH have more immature Sertoli cells as they in theory would produce higher levels of AMH than mature Sertoli cells [ 3 , 11 ]. Moreover, our findings are in accordance with a recent study showing that serum AMH is positively associated with sperm production, serum FSH, and serum inhibin B in a cohort of normozoospermic men [ 12 ]. Several other studies have measured serum AMH in both fertile and infertile men but most of these cohorts are relatively small.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ideally, the observed differences in reproductive hormones between AMH groups could be supported by evaluation of testis histology, but despite this limitation, it is unlikely that men with low serum AMH have more immature Sertoli cells as they in theory would produce higher levels of AMH than mature Sertoli cells [ 3 , 11 ]. Moreover, our findings are in accordance with a recent study showing that serum AMH is positively associated with sperm production, serum FSH, and serum inhibin B in a cohort of normozoospermic men [ 12 ]. Several other studies have measured serum AMH in both fertile and infertile men but most of these cohorts are relatively small.…”
Section: Discussionsupporting
confidence: 93%
“…However, the association between serum AMH and sperm production was not inferior to the link found with serum inhibin B and sperm production. Furthermore, serum AMH was strongly associated with serum inhibin B and serum FSH, which are in line with previous studies [ 4 , 12 , 14 ] and support that serum AMH is a marker of Sertoli cell function. We found that combined low levels of serum AMH and high levels of serum FSH tend to be a better marker for semen quality compared to AMH alone, though only found in up to 16% of infertile men referred for andrological workup prior to ICSI.…”
Section: Discussionsupporting
confidence: 92%
“…Antimüllerian hormone (AMH) is an indicator for detecting ovarian function, but it is also one of the most important indicators for evaluating male fertility. It has been shown that AMH levels are positively correlated with total sperm count, concentration, and forward motility [29]. In this study, the serum levels of these hormones were determined at two different months of age in Qianbei goats, and the levels at age 9 months were all extremely signi cantly higher than those at age 3 months (P < 0.01).…”
Section: Discussionmentioning
confidence: 66%
“…Luteinizing hormone (LH) promotes testicular development and eventual maturation of spermatogenesis [28], and follicle-stimulating hormone (FSH) has a major role in males by acting synergistically with testosterone to maximize sperm production [29]. Studies have shown that AMH levels are positively correlated with total sperm count, concentration and positive motility [30]. In this study, the serum levels of these hormones were determined at two different months of age in Qianbei Ma goats, and the levels at age 9 months were all extremely significantly higher than those at age 3 months (P < 0.01), which was similar to the study of Zhang [7].…”
Section: Discussionmentioning
confidence: 99%